Stability and performance investigations of model predictive controlled active-front-end (AFE) rectifiers for energy storage systems - Akter M.P.; Mekhilef S.; Tan N.M.L.; Akagi H. (Korean Institute of Power Electronics, 2023)
Controllers; Cost functions; Dynamic response; Electric power distribution; Electric power factor; Electric rectifiers; Energy storage; Model predictive control; Predictive control systems; Renewable energy resources; Stability; System stability; Ac-dc power conversion; Active front ends; Efficiency comparisons; Energy storage systems; Fast dynamic response; Nonlinear simulations; Renewable energy source; Stability analysis; Rectifying circuits